A herceg Batthyány-Strattmann hitbizomány gazdasági változásai a 20. század első felében - Kaposi, Zoltán (Közép-Európai Közlemények, 2012)
The topic of the study is the transformation of the princely Batthyány-Strattman entail in the first part of the 20th century. We are seeking for the answer how could an immobile entail land system get through such a significant change. The entail was created by Count Lajos Batthyány in order to provide the wealth for the family in the long run. Even in the 19th, but mainly in the 20th century so many external impacts hit the entail which resulted an important transformation. Due to Trianon the organisation which had consisted four domestic manors lost its Ludbreg Manor, which was across the River Dráva, in Croatian territory. As a result of the land reform in 1920 and the property tax in 1921 nineteen percent of the lands were gone. The Entail Act of 1936 disengaged half of the remained agricultural lands from the traditional limitations. Finally, entail manors died out in 1945 due to the land reform. According to our research we think that the entail had been continuously loosing from its intact state and became more and more defenceless of political decisions.